Informal Settlements and Their Relationship to Crime - alhabardi, Abdulrahman; alsanea, Dr. faisal (مجلة الشرق الأوسط للعلوم الإنسانية والثقافية, 2026)
This study looks at how informal settlements expand, as well as how these settlements factor into the rising of crimes in cities. All three flows of migrating (or moving) to a city, population growth, and rapid urban planning that is weak in its design is the socio urban phenomenon. Housing policies are weak as well in their design and execution to meet the needs of ever-growing populations. The study makes the assumption that the informal populated settlements of cities have a social, structural, and economic character to them that gives the stimuli for the various forms of crimes to emerge. The economic and the violent crimes, as well the social crimes encapsulate the design of the settlements. This research study emphasizes the poverty, the many social and economic conditions that are common to these informal settlements, which include crime. The lack of employment and the education that is needed for these kinds of jobs, the sickness care and the overall structure of the community is poorly designed. The family structure within the population is weak and the social bonds are lacking. Social structure that captures the informal settlements weakens the overall social control that is needed and used to reduce crime. A descriptive-analytical method is employed to study the phenomenon through analysis of the past studies and documentation regarding the intersections of crime and informal settlements to delineate the phenomenon in a descriptive and impenetrable manner before interpreting it in relation to the socio-theoretical constructs that are most applicable. The socio-theoretical constructs are primarily based on relative deprivation theory which conceptualizes crime through the lens of the socio-psychological constructs of social alienation and perceived injustice and social control theory which posits that the absence of social structures of family and community weakens a society’s ability to control deviant behavior. This study conclusively demonstrates the correlation that exists between the extent of socio-economic deprivation in informal settlements and the crime rate in informal settlements. The primary driver of the increased crime rate within these settlements are socio-economic factors such as poverty and unemployment, which for a portion of the population economically motivates crime to supplement one’s basic necessities. The study is particularly focused on the absence of basic services, overcrowding, poor public lighting, public crime facilities, and a lack of appropriate public administration as factors that shape the extent of crime and the level of crime prevention and control. Additionally, the absence of socio-economic interventions and the lack of integration of the informal settlers into the overall urban community structure have a cumulative socioeconomic marginalization, social isolation, and informal settlements.The analysis posited that combatting crime in the informal settlements goes beyond the mere provision of security measures, and that for crime to be durably addressed, such improvements in the urban planning of the informal settlements must include the enhancement of urban infrastructure, greater educational and job provision, the maturing of civil society, and the establishment of functional collaboration between the inhabitants and the formal structures of the settlements, thereby enabling social order for the sustained reduction of crime.